Mario and Sonic at the Olympic Games: Effect of Gamification on Future Physical Education Teachers - Salvador Pérez-Muñoz; Antonio Sánchez Muñoz; José Manuel De Mena Ramos; Alberto Rodríguez-Cayetano (Applied Sciences, 2022)
Gamification is a new methodological tool in the field of physical education and sports sciences, which seeks to generate a formative change in educational centers and in the training of future teachers. The aim of the research was to analyze the effect of gamification on motivation, basic psychological needs and cooperative learning of prospective physical education teachers. The sample consisted of 102 future teachers in the specific area of physical education and sport. Three measuring instruments were used: Motivational Situation Scale, Cooperative Learning Questionnaire and Basic Psychological Needs in Physical Education Scale. The significance level (p < 0.05) was determined according to the variables described. The results were analyzed with the Kruskal–Wallis test for the variables age and study group and the Mann–Whitney U-test for gender. The results show high values for basic psychological needs, motivation and cooperative learning. In the case of cooperative learning, gamification has a different behavior according to gender. By degree, gamification does not affect the degree of study in the same way. In conclusion, the results of the present study support the use of gamification in the training of future physical education teachers, as it is associated with increased levels of students’ intrinsic and self-determined motivation, basic psychological needs and cooperative learning.